Penegakan Hukum terhadap Pelanggaran Lalu Lintas yang Menyebabkan Kecelakaan di Kabupaten Sukoharjo - Febrio Bimo Wahyu Pamungkas (Jurnal Hukum Lex Generalis, 2025)
This study examines law enforcement against traffic violations that lead to accidents in Sukoharjo Regency. Based on Law Number 22 of 2009 and related regulations, enforcement is carried out through preemptive, preventive, and repressive measures by the police. Violations such as negligence, traffic sign violations, and lack of driver discipline are the main factors in accidents. The effectiveness of law enforcement is still hampered by low public awareness and limited facilities. Improved technology, education, and cross-sector coordination are needed to reduce the number of accidents and maintain order in traffic.